MANAGEMENT OF EDUCATIONAL PROCESSES IN HIGHER EDUCATION INSTITUTIONS BASED ON INNOVATIVE PEDAGOGICAL TECHNOLOGIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article describes the content of innovative pedagogical technologies, through which the issues of improving the educational process of higher education. The classification features of pedagogical technologies in the educational process and the differences between the methodology are given.